Robot-Supported Collaborative Learning (RSCL): Social Robots as Teaching Assistants for Higher Education Small Group Facilitation - Rosenberg-Kima, Rinat B.; Koren, Yaacov; Gordon, Goren (Frontiers in Robotics and AI, 2020)
Acknowledging the benefits of active learning and the importance of collaboration skills, the higher education system has started to transform towards utilization of group activities in the classrooms. In this study, a novel interaction has been introduced, wherein a robot facilitated a small collaborative group activity of students in higher education. Thirty-six students completed a three hours activity that covered the main content of a course in Human Computer Interaction. The students worked in groups of four on three activities, where each activity entailed a different condition: paper-based interaction (with the teacher as facilitator of several groups), tablets-only interaction, and tablets and robot interaction. The robot facilitated the latter interaction by introducing the different tasks, ensuring proper time management, and encouraging discussion among the students. This study examined the effects of facilitation type on attitudes towards the activity facilitation, the group activity, and the robot, using quantitative and qualitative measures. Overall students perceived the robot positively, as friendly and responsive, even though the robot did not directly respond to the students’ verbal communications. While most survey items did not convey significant differences between the robot, tablet or teacher, we found significant correlations between perceptions of the robot and attitudes towards the activity facilitation and the group activity. Qualitative data revealed the drawbacks and benefits of the robot, as well as its relative perceived advantages over a human facilitator, such as better time management, objectivity and efficiency. These results suggest that a Robot Supportive Collaborative Learning (RSCL) is a promising novel paradigm for higher education.